Comparative performance evaluation of Horro and Menz sheep of Ethiopia under grazing and intensive feeding conditions - Kassahun, A. (Humboldt-Universität zu Berlin, 2000)
This study has been carried out at the former International Livestock Centre for Africa (ILCA), that is now the International Livestock Research Institute (ILRI) experiment station at Debre Birhan, Ethiopia. This research is part of an ILCA (now ILRI) Pan-African research programme designed to investigate and characterise genetic resistance to endoparasites in some indigenous small ruminants in sub-Saharan Africa. The present study was, therefore, undertaken in an attempt to generate information that may contribute towards the understanding of the relative performance of two highland sheep (Horro and Menz) of Ethiopia under station management conditions.